2014
DOI: 10.4012/dmj.2014-123
|View full text |Cite
|
Sign up to set email alerts
|

Use of a gelatin hydrogel membrane containing β-tricalcium phosphate for guided bone regeneration enhances rapid bone formation

Abstract: The purpose of this study was to evaluate a thin gelatin hydrogel membrane containing β-tricalcium phosphate (G-TCP) for use in guided bone regeneration, a technique that we developed. G-TCP membranes were fabricated from gelatin and β-TCP powder, freezedried, and cross-linked by heating. The resulting G-TCP membranes were as thin as collagen membranes, with high mechanical integrity. Proliferation and differentiation of rat bone marrow stromal cells (BMSCs) on G-TCP and collagen membranes were examined. On bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Different scaffolds have been utilized as growth factor carriers to optimize bioavailability and increase their half-life. Among these, collagen (9) ,gelatin sponges (10,11) , combination (sandwich membrane) (12) and chitosan (13,14) have been used as vehicles for various growth factors in bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different scaffolds have been utilized as growth factor carriers to optimize bioavailability and increase their half-life. Among these, collagen (9) ,gelatin sponges (10,11) , combination (sandwich membrane) (12) and chitosan (13,14) have been used as vehicles for various growth factors in bone regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Different scaffolds have been utilized as growth factor carriers to optimize bioavailability and increase their half-life. Among these, collagen (9) ,gelatin sponges (10,11) , combination (sandwich membrane) (12) and chitosan (13,14) have been used as vehicles for various growth factors in bone regeneration.However, a membrane prepared from gelatin alone cannot function as a GTR membrane due to its mechanical weakness. To overcome this drawback, βtricalcium phosphate (β-TCP) powder was mixed with gelatin solution, because it is osteoconductive and biodegradable.…”
mentioning
confidence: 99%
“…It has been observed that the GEL based membrane has a faster osteoconductive effect than the Col membrane in the market. The reason is thought to be caused by the combination of GEL and β-TCP [25].…”
Section: Pla and Gel Based Gbr Membrane Case Studiesmentioning
confidence: 99%
“…Histology results confirmed bone formation. However, there was no significant difference in bone volume between the two membranes when compared to the untreated control [115].…”
Section: Application Of Regenerative Scaffold For Bte and Or Regenmentioning
confidence: 99%